Basic and clinical studies of azithromycin, a new macrolide antibiotic, in the field of surgery - Nakayama, Issei (Japanese Journal of Chemotherapy, 1995)
The efficacy of a newly developed macrolide antibiotic, azithromycin (AZM), in the field of surgery, was investigated basically and clinically by means of collaborative studies conducted in 18 major institutes and their affiliated hospitals throughout Japan. The following results were obtained. 1. Assessment of pharmacokinetics: AZM levels in gallbladder tissue were 8.42μg/g and 3.92-10.4μg/g about 24 hours and 48 hours, respectively, after a single 500mg administration. Bile AZM levels reached the maximum level, 186-509 μg/ml, 2-5 hours after administration. 2. Clinical assessment: AZM was administered at a dose of 250mg (titer) or 500mg (titer) once a day for 3 days. Seven patients were excluded or dropped out, such that clinical efficacy was eventually evaluated in 179 patients. These subjects consisted of 85 with superficial purulent diseases, 13 with mastitis, 25 with periproctal abscess, 45 with superficial secondary infection due to trauma, burn and operative wound, 6 with cholecystitis or cholangitis, and 5 with other infections. The efficacy rate was 96.5%(82/85) for superficial purulent diseases, 76.9%(10/13) for mastitis, 84.0%(21/25) for periproctal abscess, and 75.6%(34/45) for superficial secondary infection due to trauma, burn and operative wound. The overall efficacy rate was 87.7%(157/179) The eradication rate was 90.1%(109/121) for gram-positive bacteria, 85.7%(36/42) for gramnegative bacteria, and 93.6%(73/78) for 241 anaerobic strains of casual bacteria, which were isolated from 140 patients. The overall eradication rate was 90.5%(218/241). Adverse reactions were observed in 6 of 181 patients in whom they were evaluated. They consisted of gastrointestinal symptoms in 5 patients and exanthema in 1. Abnormal changes in clinical laboratory test values were observed in 5 patients, and consisted of eosinophilia in 1, elevation of S-GOT and S-GPT in 1, elevations of S-GOT, S-GPT and γ-GTP in 1, elevations of S-GPT in 1, and elevations of AL-P and γ-GTP in 1. These results suggest that AZM is very useful for infections in the field of surgery.